2020
DOI: 10.5194/egusphere-egu2020-2099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of turbulent magnetic reconnection in solar flares with microwave imaging spectroscopy

Abstract: <p>Magnetic reconnection plays a central role in highly magnetized plasma, for example, in solar corona. Release of magnetic energy due to reconnection is believed to drive such transient phenomena as solar flares, eruptions, and jets. This energy release should be associated with a decrease of the coronal magnetic field. Quantitative measurements of the evolving magnetic field strength in the corona are required to find out where exactly and with what rate this decrease takes place. The only ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Landi et al (2021) found that within 22 min of flare onset the magnetic field measured with the Fe X MIT line underwent a strong enhancement at a location which later corresponded to the footpoints of post-flare loops; also, this magnetic field enhancement stored enough magnetic energy to power then entire flare, and was completely dissipated during the flare (see Figure 1). A similar conclusion has been made for an X8.3 limb flare with the imaging microwave spectroscopy technique (Fleishman et al, 2020). Frontiers in Astronomy and Space Sciences frontiersin.org…”
Section: Build Up and Dissipation Of Magnetic Energysupporting
confidence: 78%
See 2 more Smart Citations
“…Landi et al (2021) found that within 22 min of flare onset the magnetic field measured with the Fe X MIT line underwent a strong enhancement at a location which later corresponded to the footpoints of post-flare loops; also, this magnetic field enhancement stored enough magnetic energy to power then entire flare, and was completely dissipated during the flare (see Figure 1). A similar conclusion has been made for an X8.3 limb flare with the imaging microwave spectroscopy technique (Fleishman et al, 2020). Frontiers in Astronomy and Space Sciences frontiersin.org…”
Section: Build Up and Dissipation Of Magnetic Energysupporting
confidence: 78%
“…The GS emission in solar flares is characterized by a spectrum that typically has a spectral peak at the microwave range, while falls following roughly power-laws towards lower and higher frequencies. Supplementary videos to (Fleishman et al, 2020) display dependence of the GS spectrum on the key physical parameters including the high-energy cut-off of the nonthermal electron spectrum. This high-energy cut-off mainly affects the high-frequency end of the GS spectrum.…”
Section: High-energy End Of the Accelerated Electron Spectra In Solar...mentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific potential of ALMA observations of the Sun is promising but requires significant effort and resources to be fully unlocked due to the complexity of the instrument and the observational targets, namely, the dynamic and intermittent chromosphere, both in a quiescent and active state, the atmosphere above ARs including the often dramatically evolving coronal magnetic field (Fleishman et al, 2020), and non-thermal electrons in solar flares (Fleishman et al, 2021b). The resulting challenges for numerical modeling of the chromosphere, prominences, and the flaring corona, their appearances at the wavelengths observed using ALMA, and not least, the impact of ALMA's complex instrumental properties pose critical tests of our current understanding that will inspire future progress.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4E in Chen et al (2020b), see also Bastian et al (1998)]. We have therefore adopted the gyrosynchrotron (GS) forward fit method described in Fleishman et al (2020) to fit the brightness temperature spectrum T B (ν) using an isotropic non-thermal electron source with a power-law energy distribution. We restricted our spectral fit to frequencies above 2 GHz only, as the spectrum below 2 GHz contains contributions from coherent radiation (Bastian et al, 1998).…”
Section: Sources Of Radio Emissionmentioning
confidence: 99%